2001
DOI: 10.1183/09031936.01.17202870
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroids reduce growth. Or do they?

Abstract: The class label warning in the United States for inhaled corticosteroids (ICS's) states that these drugs may reduce growth velocity in children. In this paper, the evidence for this warning is reviewed from a clinical point of view.Children with asthma tend to grow slower than their healthy peers during the prepubertal years because they go into puberty at a later age. However, asthmatic children do achieve a (near) normal adult height. In randomized controlled clinical trials, the use of inhaled beclomethason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 63 publications
2
15
0
2
Order By: Relevance
“…24,30 The continuous treatment of patients with asthma through inhaled medicine provides safe and effective long-term disease management. 45 Studies have suggested an association of superior COC with fewer ED visits in different populations with asthma. 23,26,30,41,46 Our findings are consistent with those reported in a previous study focusing on children.…”
Section: Discussionmentioning
confidence: 99%
“…24,30 The continuous treatment of patients with asthma through inhaled medicine provides safe and effective long-term disease management. 45 Studies have suggested an association of superior COC with fewer ED visits in different populations with asthma. 23,26,30,41,46 Our findings are consistent with those reported in a previous study focusing on children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies designed to evaluate growth in asthmatic children have shown that growth rates are commonly reduced during the first months of ICS treatment, but that this does not affect adult height [36]; thus, a negative effect on adult height is unlikely. Error bars represent SEM.…”
Section: Withdrew During Run-in (N=78mentioning
confidence: 99%
“…Kortikosteroid inhalasi yang paling sering digunakan adalah beklometason. 6 Sediaan kortikosteroid yang sering kita kenal antara lain tertera pada Tabel 1.…”
Section: Sediaan Kortikosteroid Inhalasiunclassified
“…Faktor ini penting pada anak karena jumlah obat yang ditelan lebih besar daripada yang dihirup (Gambar 1). 5,6 Pada saat obat diabsorbsi akan terjadi efek secara sistemik yang tergantung dari jumlah obat yang diabsorbsi, potensi, dan farmakokinetik obat. 5,7,.8 Sehingga dalam memberikan kortikosteroid inhalasi sebaiknya dalam dosis di bawah dari dosis yang menimbulkan efek sistemik.…”
Section: Bioavailibilitas Kortikosteroid Inhalasiunclassified